FAKTOR–FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Trisnawati Trisnawati; Henny Setyo Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2017)
This research is conducted to find the factor’s affecting firm performance of non financial listed in Indonesia Stock Exchange. The sample was taken from 101 companies in the last five years from 2010-2014. The dependent variable in this research is the firm performance measured by return on equity, while the independent in this research is leverage measured debt to equity, growth opportunity, firm size, and liquidity. The results show that there are negative and significant influence between research leverage to firm performance. There is also posifive and significant effect between firm size to firm performance. And there is no influence between growth opportunity and liquidity to firm performance.